Generative production and evaluation of ornamental plant potential of an endemic flax species for ecological landscape applications - Erken, Kamil (Wiley, 2023)
The flax genus consists of several natural species, which have the potential as ornamental plants for ecological landscape applications. Linum pamphylicum subsp. olympicum is an endemic, naturally occurring flax species that can only be found in Bursa, Turkey. The aim of the study is to examine the morphological and biological characteristics of L. pamphylicum subsp. olympicum in relation to its cultivation and ornamental plant potential, and to reveal the best germination practices, as well as to establish an ex situ conservation garden. According to the results, in natural conditions, L. pamphylicum subsp. olympicum taxon forms a spreading habitus that is resistant to infertile and arid soil conditions. It covers the soil surface with an average width of 40.50 cm and average height of 16.63 cm foliage. It grows an average of 50.80 annual flowering branches. It is a natural taxon that draws attention with its bright yellow and long-lasting flowers. Germination of L. pamphylicum subsp. olympicum seeds suffers due to physical and physiological dormancy. By this study, the germination of L. pamphylicum subsp. olympicum seeds was improved up to 92.33% by using 4000 ppm gibberellic acid (GA(3)) treatments. Both cold-wet stratifications with soaking in 4000 or 2000 ppm GA(3) provided the fastest germination speed of T-50 = 14 days. With the current study germination of L. pamphylicum subsp. olympicum seeds was improved significantly, the phenological and morphological characteristics were determined and a seed resource garden was established for ornamental plant studies.
Keywords: germination; gibberellic acid; Linum pamphylicum subsp olympicum; stratification; ultrasonic wave